Study the Stylistics of "Ashbah" sermon of "Nahjol Balaqeh" - Rahmani, Atefeh; Pashazanoos, Ahmad (Journal of History Culture and Art Research, 2017)
Stylistics study the language features of literary text and try to use the tools of linguistics in order to reveal the effects of the beauty of a literary work and public property of it. Such studies are looking for common points in all literary works of scholar which can be fulfilled with studying a part of his works and sometimes explore the effects of stylistics on a certain theme by means of stylistics tools and because stylistics researches often have arbitrary and relative laws that study in this area depends on the nature of critic and taste. In this study it was tried to investigate the coordination of choice of words with sound and sentence structure, vocabulary eloquence and coordination of the structure of sentences with content, to indicate that in this sermon all three levels: phonology, syntax and lexicon have been used to represent the proportion of words and meaning.